Review of the European species of the genus Anagrus Haliday (Hymenoptera Chalcidoidea) (Bollettino di zoologia agraria e bachicoltura, 2024)
The author has reviewed the European species of Anagrus Haliday genus.The specimens of the Debauche, Soyka and Walker collections were examined together with other specimens collected by the author. A. nigriceps (Smits van Burgst), A. incarnatus fuscus Botoc and an unnamed species keyed by Graham (1982) were not studied and therefore not included in this review.The genus is subdivided into 3 subgenera: Paranagrus Perkins, Anagrella Bakkendorf and Anagrus Haliday s. str .. This last subgenus is itself subdivided in 2 groups: the "atomus" and "incarnatus" species group.Tue characters used in species descriptions are discussed.The following species are considered to occur in Europe: A. arcuatus Soyka, A. avalae Soyka, A. bakkendorfi Soyka, A. breviphragma Soyka, A. brocheri Schultz, A. dilatatus Soyka, A. ensifer Debauche, A. fennicus Soyka, A. incarnatus Haliday, A. incarnatosimilis Soyka, A. obscurus Foerster sensu Soyka, A. obvius Soyka, A. similis Soyka, A. subfascus Foerster sensu Debauche, A. supremosimilis Soyka, A. ustulatus Haliday, A. valkenburgensis Soyka.A key to females and descriptions of the species are given.The following species have been placed in synonymy: Anagrus devius Soyka, Anagrus gabitzi Soyka, Anagrus hundsheimensis Soyka, Anagrus kressbachi Soyka, Anagrus lemonicolor Soyka, Anagrus levis Soyka, Anagrus stammeri Soyka and Anagrus varius Soyka with Anagrus atomus (L.); Anagrus parvus Soyka with Anagrus ustulatus Haliday; Anagrus ovipositor Soyka, Anagrus supremus Soyka, Anagrus vacuipennis Soyka and Anagrus longigaster Soyka with Anagrus breviphragma Soyka; Anagrus latipennis Soyka with Anagrus bakkendorfi Soyka; Anagrus diversicornis Soyka with Anagrus avalae Soyka; Anagrus longus Soyka with Anagrus obvius Soyka; Anagrus latior Soyka and Anagrus andreae Soyka with Anagrus brocheri Schulz; Anagrus holci Walker with Anagrus similis Soyka; Anagrus neopallidus Soyka and Anagrus pallidior Soyka with Anagrus incarnatus Haliday; Anagrus danicus Soyka, Anagrus pulcher Soyka, Anagrus pulcherrimus Soyka, Anagrus varicolor Soyka, Anagrus mutans Walker and Anagrus stenocrani Walker with Anagrus incarnatosimilis Soyka.
Keywords: Mymaridae; Anagrus; taxonomy